THU0246 Subcutaneous Abatacept: Long-Term Data From the Acquire Trial. (23rd January 2014) - Alten, R.; Pacheco-Tena, C.; Covarrubias, A.; Leon, G.; Mysler, E.; Keiserman, M.; Valente, R.; Nash, P.; Simon-Campos, J.; Box, J.; Legerton, C.; Nasonov, E.; et al.
Abstract : Background: The Abatacept (ABA) Comparison of Sub[QU]cutaneous (SC) versus Intravenous (IV) in Inadequate Responders to MethotrexatE (MTX) (ACQUIRE) study showed comparable efficacy and safety of SC vs IV ABA over 6 mths. 1 Objectives: To present 32-mth safety and efficacy data from the long-term extension (LTE) of ACQUIRE, during which all patients (pts) received SC ABA. Methods: ACQUIRE was a Phase IIIb, 6-mth, double-blind (DB) study in which pts with active RA (³10 swollen and ³12 tender joint count [SJC and TJC], C-reactive protein (CRP) ≥0.8 mg/dL) refractory to MTX received IV or SC ABA, plus MTX, followed by an open-label LTE when pts received SC ABA 125 mg/wk. Not all pts had reached later time points at time of analysis, as a result of differential enrolment in the trial. Results: Of 1372 pts entering the LTE, 1134 (82.7%) remained on therapy at time of reporting. Mean baseline RA duration was 8 yrs, TJC and SJC were 30 and 20, respectively, and HAQ-DI was 1.7. Median (range) ABA exposure was 33 (8–44) mths. The incidence rate (IR; events/100 pt-yrs) of serious adverse events for pts treated with SC ABA in the LTE (8.76 [95% CI: 7.71–9.95]) was comparable with that for SC ABA in the DB period (9.02 [6.31–12.90]) and did not increase with increasing exposure. The IR of overall and serious infections in the LTE (44.80 [41.81–48.01] and 1.72 [1.30–2.27], respectively) did not increase vs the DB period (84.62 [74.50–96.11] and 1.48 [0.62–3.56], respectively). Bacterial, viral and hospitalised infections occurred at IRs of 27.28 (25.16–29.57), 18.25 (16.61–20.06) and 1.55 (1.16–2.07) during the LTE. The IR of malignancy did not increase in the LTE (1.19 [0.86–1.66]) vs the DB period (0.59 [0.15–2.36]). Injection-site reactions occurred in 27 (2.0%) pts in the LTE (none serious) and 19 (2.6%) pts in the DB period. Overall, 139/1365 (10.2%) and 1/153 (0.7%) pts experienced immunogenicity during the LTE and DB periods, respectively. ACR responses were maintained and comparable with original SC and IV groups: at Day 169, ACR 20 response rates were 80.2% (95% CI: 77.2, 83.2) and 80.0% (77.0, 83.0) and at Day 981 were 84.8% (80.8, 88.8) and 84.7% (80.7, 88.8). DAS28 (CRP) <2.6 rates (95% CI) were 24% (21–27; n=685) and 25% (22–28; n=667) at Day 169, and 39% (33–44; n=288) and 35% (29–40; n=275) at Day 981 for the original SC and IV groups, respectively. HAQ-DI responses (change from baseline ≥0.3) were 73% (95% CI: 69–76; n=691) and 68% (65–72; n=672) at Day 169, and 74% (69–79; n=313) and 70% (65–75; n=303) at Day 981 for the original SC and IV groups, respectively. Conclusions: Over 32 mths, SC abatacept showed consistent safety with high patient retention. ACR, HAQ-DI response and DAS28 remission rates were maintained through the LTE. References: Genovese MC, et al. Arthritis Rheum 2011;63 :2854–64 Disclosure of Interest: R. Alten Grant/research support from: BMS, Merck Pharma GmbH, Wyeth Pharmaceuticals, Pfizer, Consultant for: Abbott Laboratories, Horizon Pharma, Merck Pharma GmbH, Nitec Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, Speakers bureau: Abbott Laboratories, BMS, Horizon Pharma, Merck Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, C. Pacheco-Tena: None Declared, A. Covarrubias Shareholder of: UNIDAD REUMATOLOGICA LAS AMERICAS SCP, Grant/research support from: BMS, Pfizer, Lilly ICOS, G. Leon: None Declared, E. Mysler Grant/research support from: BMS, Consultant for: BMS, Speakers bureau: BMS, M. Keiserman Grant/research support from: Abbott Laboratories, Biogen Idec, Bristol-Myers Squibb, Eli Lilly and Company, Human Genome Sciences, Inc., MSD, Pfizer Inc, Roche, UCB, Inc, Novartis, Consultant for: Abbott Laboratories, Bristol-Myers Squibb, MSD, Speakers bureau: Bristol-Myers Squibb, MSD, R. Valente Grant/research support from: Pfizer, UCB, BMS, Roche, Takeda, Lilly, P. Nash Grant/research support from: BMS, Consultant for: BMS, Speakers bureau: BMS, J. Simon-Campos: None Declared, J. Box Shareholder of: Box Arthritis and Rheumatology of the Carolinas PLLC, Consultant for: BMS, Speakers bureau: BMS, C. Legerton III Consultant for: BMS, E. Nasonov Speakers bureau: Roche; Bristol-Myers Squibb Company; Abbott Laboratories; Merck Sharp & Dohme Corp; UCB Pharma, Inc, P. Durez Speakers bureau: BMS, I. Delaet Shareholder of: BMS, Employee of: BMS, M. Genovese Consultant for: Bristol-Myers Squibb